1983
DOI: 10.1128/jcm.18.1.110-114.1983
|View full text |Cite
|
Sign up to set email alerts
|

Detection of two Blastomyces dermatitidis serotypes by exoantigen analysis

Abstract: We evaluated the diagnostic value of antibody to Blastomyces dermatitidis A precipitin arcs for identifying B. dermatitidis cultures by the exoantigen technique with 88 isolates from the United States and Canada, 12 from Africa, and 1 each from India and Israel. In addition, we studied 190 mycelial-form isolates of other fungi which could be confused antigenically or morphologically with B. dermatitidis. Antigen extracts from all of the North American isolates, the Indian and Israeli isolates, and one of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 12 publications
(10 reference statements)
3
24
1
Order By: Relevance
“…When probing with blastomycosis dog serum in a Western blot, both the T-58 and ERC-2 lysates displayed a major band in the molecular weight range previously described for Antigen A and WI-1 [10][11][12]. The Zaire lysates had no observable bands in this range (Fig.…”
Section: Western Blotmentioning
confidence: 57%
See 3 more Smart Citations
“…When probing with blastomycosis dog serum in a Western blot, both the T-58 and ERC-2 lysates displayed a major band in the molecular weight range previously described for Antigen A and WI-1 [10][11][12]. The Zaire lysates had no observable bands in this range (Fig.…”
Section: Western Blotmentioning
confidence: 57%
“…Previous studies had shown that most African B. dermatitidis isolates did not have the major antigen found in North American B. dermatitidis, Antigen A. These have been designated serotype 2 [10][11][12]. Both the rabbit and dog sera assays indicated that the 48089 lysate did not have the same antigenicity as the other lysates, and this implied that this lysate might be serotype 2.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study (2) found that African isolates of Blastomyces dermatitidis required repeated subculturing onto fresh cottonseed agar to convert them from their mycelial to yeast form at 37 "C. At least three successive subcultures onto fresh medium every 10 days were required before complete conversion was obtained. Because of the success reported by Kane (1) with a partially defined medium, namely, Tween-albumin-niacin agar supplemented with casamino acids (KT), in converting mycelial North American isolates of B. dermatitidis to yeast form at 37 "C within 72 h, we decided to evaluate the KT medium.…”
Section: Introductionmentioning
confidence: 99%